The Fishing Ground of Bottom Longline Vessels and Exploitation Rate of Tiger Grouper (Epinephelus aerolatus) in Arafura Waters - Andina Ramadhani Putri Pane; Reza Alnanda; Prihatiningsih Prihatiningsih; Hufiadi Hufiadi; Ali Suman (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2020)
As excessive capture activity adversely impacts fisheries sector, fish resources management is a necessity. This study was conducted as a scientific contribution for the managements of bottom longline fisheries in Arafura Waters and areolate grouper (Epinephelus areolatus) as one of the target catches. It was carried out from February to December 2017 and in November 2018. Data on the fishing grounds of eight bottom longline vessels were obtained from the vessel monitoring system (VMS) of Probolinggo Marine and Fisheries Resources Supervisory Unit, Mayangan Probolinggo Fishing Port, and Marine and Fisheries Resources Surveillance (PSDKP) Tual Station. Based on the analysis of the coordinates from the VMS, the fishing grounds of the bottom longline vessels in Arafura waters were found around Dolak until the border with Merauke and around Timika until Aru Islands. The composition of dominant catches consisted of croaker (Pennahia spp.) and snapper (Lutjanus spp.), as well as grouper (Epinephelus spp.) in a smaller proportion. The size structure of the areolate grouper caught with bottom longlines was 21.5–54.5 cmTL; its length at first capture (Lc) was 33.9 cmTL; and its asymptotic length was 70.5 cmTL. Its growth rate (K) was found 0.26 per year. The fishing mortality (F) of the species was found higher than its natural mortality (M), and its exploitation level (E) was 0.74, meaning that the species was already overfished. The exploitation should be reduced by 40–50% to keep the fish resources in Arafura sustainable, especially for areolate grouper. Keywords: fishing ground, bottom longline, exploitation level, tiger grouper, Arafura